Methylotrophs inhabit the human mouth. In this study, methylotrophic bacteria were isolated from the human mouth microflora of 63 subjects, especially from the tongue, gingival, and subgingival area using minimal agar supplemented with 1% methanol. The obtained isolates were subjected to biochemical assays, continued with antibiotics susceptibility testing using ampicillin (10 mg), tetracycline (20 mg), kanamycin (30 mg), trimethoprim (5 mg), and streptomycin (10 mg). Genetic diversity was analy - DIANA ELIZABETH WATURANGI; IVANA FRANCISCA IVANA FRANCISCA; CINDY OKTAVIA SUSANTO (HAYATI Journal of Biosciences, 2011)
Methylotrophs inhabit the human mouth. In this study, methylotrophic bacteria were isolated from the human mouth microflora of 63 subjects, especially from the tongue, gingival, and subgingival area using minimal agar supplemented with 1% methanol. The obtained isolates were subjected to biochemical assays, continued with antibiotics susceptibility testing using ampicillin (10 mg), tetracycline (20 mg), kanamycin (30 mg), trimethoprim (5 mg), and streptomycin (10 mg). Genetic diversity was analyzed using ARDRA method. Isolates varying in morphology characteristics were amplified for 16S rRNA gene and continued with DNA sequencing. As many as 21 methylotrophic bacterial isolates were purified and divided into seven groups with different phenotypic profiles. A majority of the isolates were resistant to trimethoprim but sensitive to kanamycin, streptomycin, and tetracycline. Resistance to ampicillin was variable in each isolate. ARDRA showed nine different digestion profiles. DNA sequencing analysis of the 16S rRNA gene showed that six isolates with different phenotypic and digestion profiles were closely related to Methylobacterium radiotoleran (94%), Microbacterium esteraromaticum (99%), Pseudomonas sp. (100%), and three of them were exhibited 99, 99, and 98% sequence similarity with Gordonia sp., respectively. The results of this study revealed diversity among methylotrophic bacteria particularly in human mouth.